Sulfuric acid plant (Miagao, Iloilo, Philippines University of the Philippines School of Science and Technology, 2013)
A plant was deign was done for the production of 99.5% m/m sulfuric acid from solid amd molten sulfur.
Sotech thesis.
Keywords: Sulfuric acid